JSTOR : a history - Schonfeld, Roger C., 1977- (Princeton University Press, 2003)
Ten years ago, most scholars and students relied on bulky card catalogs, printed bibliographic indices, and hardcopy books and journals. Today, much content is available electronically or online. This book examines the history of one of the first, and most successful, digital resources for scholarly communication, JSTOR. Beginning as a grant-funded project of the Andrew W. Mellon Foundation at the University of Michigan, JSTOR has grown to become a major archive of the backfiles of academic journals, and its own nonprofit organization.